COVID-19—Conspiracy or Not? Some Thoughts on Bauer and Bobrow - Walach, Harald (Journal of Scientific Exploration, 2022)
I am pleased about the discussion which my review of Kennedy’s book “The Real Anthony Fauci” has stimulated. It is a signature of the COVID-19 crisis that scientific discourse has broken down. There seem to be only two camps, those that “believe” in the mainstream narrative that COVID-19 is a deadly killer virus with far above average Case Fatality Rates that could only be halted by drastic non-pharmaceutical interventions such as complete lockdowns, stay-at-home orders, mask mandates; for which no treatment existed; which had to be spotted early by broad coverage of PCR-tests even of asymptomatic people; for which the emergency use admission of rapidly developed, badly tested vaccinations was the only and thus legally warranted action. And on the other side the “conspirationists”: those who think that the whole story was overblown, that the virus was manufactured, either by China or some other secret service, to trigger a crisis that either served the pharmaceutical industry in developing and marketing a completely new brand of preventive pharmaceuticals, m-RNA and vector vaccines; and/or to issue vaccine passports that serve the larger purpose of having complete control of the population in a China-style system of social compliance points that allow to access privileges such as travel, holidays, etc.; or even a coup d’états serving to abolish our democratic system. This thinking in camps is obvious in the public discourse in the large mainstream media, TV and print. It is obvious in the scientific discourse, where critical voices are sidelined into small outlets or penalized by retractions. It is obvious in the discussion between Bobrow, myself and Bauer, with Bauer holding a middle ground by admitting to human incompetency as the most likely factor of the crisis (which I sympathize with but won’t discuss further). I will by no means be able to address all these points in a short commentary. Especially, I will not get into the HIV/AIDS-debate, as this is probably even more complicated than the COVID-19 debate. But let me pick out a few obvious points.